THE SPECIFIC OF SOCIAL WORK WITH DISABILED CHILDREN AND THEIR FAMILIES (Bulletin of Taras Shevchenko National University of Kyiv. Social Work, 2020)
The article deals with an issue of activity of the social centers for families, who have disabled children. The author emphasize that each type of disability causes different specifics of family life, wich state social service do not pay much attention. Most part of services which are provided focuses mostly on mass work and do not afford enough possibilities of work with individual case. Activities aimed at large number of people on the one hand contributes to the communication of families and their active inclusion in social life, but on the other hand the decrease the level of individuality of each article. The article provides an analysis of services based on their relevance to the characteristics of disabled children: the duration of activities, the involvement of parents, developing the potential of activities.
Keywords: state centers of social services, disabled children, caring families, social work with families.